Surface textures and other features of diamonds - Robinson, Derek Nigel (Department of Geological Sciences, 2017)
The results of the study of more than 11 000 diamonds, from thirty kimberlite and placer deposit localities, are reported. Forty-one pristine surface textures are distinguished, including twelve which are described for the first time. Only two surface textures are ascribed to crystal growth. The others are considered to result from crystal resorption and etching although internal features, such as growth stratification and dislocation planes, are expressed in some cases. The results of etching experiments on diamond are reviewed. Oxidation is considered to be responsible for most of the resorption and etching of diamonds in nature and neither pure graphitization nor dissolution appears to be important.